Political Parties in Indonesia (1945–1950) (Journal of the College of Basic Education, 2026)
This research, titled "Political Parties in Indonesia (1945–1950)", explores the political and ideological transformations that shaped Indonesia in the immediate post-independence period. It focuses on the pivotal role played by the major political parties—namely the Indonesian National Party (PNI), the Islamic Masjumi Party, and the Indonesian Communist Party (PKI)—in redefining the structure and identity of the emerging state.The study begins with an analysis of the historical context in which a new national consciousness emerged following the revolution. It then examines how these parties functioned as tools for political mobilization, power redistribution, and the articulation of modern statehood. The research further investigates the ideological frameworks, organizational structures, and public narratives employed by each party, while addressing the institutional and cultural challenges they faced in a socially and religiously diverse society.Ultimately, the study offers a critical assessment of the foundational phase of party politics in Indonesia, questioning the extent to which these movements succeeded in translating revolutionary aspirations into inclusive national projects.